B‐cell intrinsic TLR7 signals promote depletion of the marginal zone in a murine model of Wiskott–Aldrich syndrome. Issue 10 (31st August 2015) - Kolhatkar, Nikita S.; Scharping, Nicole E.; Sullivan, Jenna M.; Jacobs, Holly M.; Schwartz, Marc A.; Khim, Socheath; Notarangelo, Luigi D.; Thrasher, Adrian J.; Rawlings, David J.; Jackson, Shaun W.
<x xml:space="preserve">Abstract</x> Patients with Wiskott–Aldrich syndrome (WAS) exhibit prominent defects in splenic marginal zone (MZ), resulting in abnormal T‐cell‐independent antibody responses and increased bacterial infections. B‐cell‐intrinsic deletion of the affected gene WAS protein (WASp) markedly reduces splenic MZ B cells, without impacting the rate of MZ B‐cell development, suggesting that abnormal B‐cell retention within the MZ accounts for MZ defects in WAS. Since WASp regulates integrin‐dependent actin cytoskeletal rearrangement, we previously hypothesized that defective B‐cell integrin function promotes MZ depletion. In contrast, we now report that B‐cell‐intrinsic deletion of the TLR signaling adaptor MyD88 is sufficient to restore the MZ in WAS. We further identify TLR7, an endosomal single‐stranded RNA (ssRNA) receptor, as the MyD88‐dependent receptor responsible for WAS MZ depletion. These findings implicate spontaneous activation of MZ B cells by ssRNA‐containing self‐ligands (likely derived from circulating apoptotic material) as the mechanism underlying MZ depletion in WAS. Together, these data suggest a previously unappreciated role for B‐cell intrinsic TLR signals in MZ homeostasis, of relevance to both pathogen responses and to the development of systemic autoimmunity.